A internet como espaço de ação para prática da cidadania ativa: análise de conteúdo do movimento contra corrupção - Romani, Douglas Ribeiro (2014)
This paper aims at examining whether the internet is a resource for strenghthening citizenship and establishing a Public Communication channel. Based on theoretical construct that defines and deepens the concepts of citizenship and Public Communication, a detailed analysis about the internet was carried out in order to understand the characteristics of this new communication platform and the structural modifications and possibilities it has brought about. Since the Internet permeates the life of every citizen and interferes, directly or indirectly, in the economic, political and cultural aspects of society, we seek to understand whether the world wide web, especially social networks, grants voice to minorities and serves as mediator in a dialogue between these individuals and the State. Therefore, this paper examines the Movimento Contra Corrupção and its Facebook webpage especially devoted to the discussion of the issue, and to society’s manifestation regarding the behavior and decency of the politicians in Brazil. Thus, a content analysis of its main posts, between the months of May and September 2013, is carried out. This was the period of when several demonstrations swept the country and the MCC movement was most active: they fostered the population’s participation and adherence to the cause. By analyzing the results, the study presents some outlines to the practice of Public Communication in contemporary society.